2016
DOI: 10.18632/oncotarget.13077
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of differentially expressed proteins in epithelial ovarian cancers using quantitative proteomics

Abstract: Ovarian cancer is the most lethal gynecological malignant tumor because of its high recurrence rate. In the present work, in order to find new therapeutic targets, we identified 8480 proteins in thirteen pairs of ovarian cancer tissues and normal ovary tissues through quantitative proteomics. 498 proteins were found to be differentially expressed in ovarian cancer, which involved in various cellular processes, including metabolism, response to stimulus and biosynthetic process. The expression levels of chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…As noted above, possible functional roles in tumor progression are incompletely understood and may differ depending upon the tumor type. In EOC, CLIC1 may be involved in cell cycle regulation and drug resistance 30 , while CLIC4 may have roles in fibroblast activation 29 . While CLIC1 has generally been associated with tumor progression in prior studies 32 , 34 , 38 , there are some contradictions regarding the role of CLIC4 in tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, possible functional roles in tumor progression are incompletely understood and may differ depending upon the tumor type. In EOC, CLIC1 may be involved in cell cycle regulation and drug resistance 30 , while CLIC4 may have roles in fibroblast activation 29 . While CLIC1 has generally been associated with tumor progression in prior studies 32 , 34 , 38 , there are some contradictions regarding the role of CLIC4 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that CLIC1 and CLIC4 may play roles in altering the EOC tumor microenvironment and affecting EOC tumor progression. CLIC4 regulated TGFβ-mediated activation of fibroblasts in EOC 29 and knocking down CLIC1 arrested EOC cell division at the G1 phase, inhibited xenograft growth in vivo , and increased susceptibility of the EOC cells to cisplatin and ROS exposure 30 .…”
Section: Introductionmentioning
confidence: 99%
“…CLIC1 is overexpressed in several cancers including liver cancer, gall bladder cancer, pancreatic ductal adenocarcinoma, glioma, breast cancer, nasopharyngeal carcinoma, and gastric cancer to name a few (Wulfkuhle et al, 2002;Petrova et al, 2008;Chang et al, 2009;Wang et al, 2009Wang et al, , 2018Tang et al, 2012;Wei et al, 2015;Jia et al, 2016;Qu et al, 2016). It is known to play a role in cell viability, possibly by modulating mitochondrial function.…”
Section: Clic1mentioning
confidence: 99%
“…Along with CLIC4, CLIC1 is a promising biomarker for epithelial ovarian cancer where its expression predicts patient survival (Singha et al, 2018). CLIC1 is shown to regulate the redox-sensitivity of ovarian cancer cells and is predicted to be a potential marker for lymphoblastic leukemia (Qu et al, 2016;Dehghan-Nayeri et al, 2017;Singha et al, 2018). Modulation of CLIC1 expression by micro RNA, hsa-mir-372 predicts the poor prognosis of patients affected with gall bladder cancers (Zhou et al, 2017) and is important for the migration and invasion of gall bladder cancer cells (He et al, 2018).…”
Section: Clic1mentioning
confidence: 99%
“…Other CpG sites located in CPT1A (cg17058475), ABCG1 (cg27243685, cg01881899 and cg10192877) and LGALS3BP (cg25178683, cg11202345, cg14870271, cg17836612 and cg27470213) were also identified in some of the studies. In the literature, the expression of CPT1A, ABCG1, SREBF1 and LGALS3BP has been associated with obesity (50-54) and linked to various cancers (55)(56)(57)(58)(59)(60)(61)(62), including breast cancer (63-69) adding plausibility to the findings. Indeed, CPT1A was recently found to be up-regulated in co-cultured adipocytes isolated from human breast adipose tissue with hormone receptor-positive or -negative breast cancer cells (70).…”
Section: Discussionmentioning
confidence: 97%